2009
DOI: 10.1080/13668800802627934
|View full text |Cite
|
Sign up to set email alerts
|

Participating in community research: exploring the experiences of lay researchers in Bradford

Abstract: Considerable attention has been given in recent years to the merits of involving community members in the research process and the resulting benefits in terms of research outcomes. Far less is known about the experiences of individuals taking on the role of lay researchers within their own community. This research investigates the experiences of six young Asian women who, following training, undertook a community health needs assessment in a neighbourhood in Bradford. Semi-structured interviews were conducted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 29 publications
1
32
0
1
Order By: Relevance
“…Patient empowerment Knowledge of community needs (empathy), services available, motivation to help community (citizenship literacy) [28] Patients motivated to take interest in community, developed greater empathy and understanding of others in community [62] Improved 'citizenship' literacy [45] None reported…”
Section: Hypothesized Impacts Suggested Dimensions To Measure Qualitamentioning
confidence: 99%
See 1 more Smart Citation
“…Patient empowerment Knowledge of community needs (empathy), services available, motivation to help community (citizenship literacy) [28] Patients motivated to take interest in community, developed greater empathy and understanding of others in community [62] Improved 'citizenship' literacy [45] None reported…”
Section: Hypothesized Impacts Suggested Dimensions To Measure Qualitamentioning
confidence: 99%
“…Patient or community research knowledge, skills and capacity [10,18,41,44,47,49,59] Increased learning of new skills (including research skills) and knowledge on topic area [18] Increased learning by patients [38] Increased knowledge and skills, putting learning/training into practice and raised awareness of issues and services [25] Enhanced teamwork skills [45] None reported Self-empowerment, increased selfconfidence, feeling of being valued and making a contribution [10,18,21,24,31,34,35,38,39,44,51,54,55,63,64] Increased confidence/sense of personal achievement [45] Equal status on project team, ownership of services being received, social support, increased confidence and self-esteem [25] None reported Impact on mental health of patients [62] Improved emotional health feel valued and involved and having activities to look forward to [25] Enhanced outlook on life [45] Development of patients' pride and ownership of their work [62] None reported…”
Section: Hypothesized Impacts Suggested Dimensions To Measure Qualitamentioning
confidence: 99%
“…This research gives further insight into the adoption of researcher roles and what participating means for those who actually do it. This exploration of the Objective 1 setting found that a number of different researcher roles were adopted and this resulted in a variety of perceived benefits, similarly reported by Newell and South (2009). Problems were also reported, akin to those already described in much of the literature and these were experienced irrespective of the level of participation of individuals and their differential roles.…”
Section: Discussionmentioning
confidence: 81%
“…South et al (2012) also call for attention to be given to the difference between formal and informal roles, as well as spectrums of participation along which researcher roles are located. Thus, more analysis is needed particularly in relation to the unquestioned assumptions reported about the positive experiences of lay researchers within numerous studies (Newell & South 2009, see Rowe 2006, Kai and Hedges 1999, Rhodes et al 2000. It may also be the case that there has simply been a lack of consideration of the issues associated with the personal implications of working within a lay researcher role (Newall and South 2009).…”
Section: Introductionmentioning
confidence: 99%
“…15,22,26,31 In particular, individuals from vulnerable groups (defined through common social and/or geographical interests/characteristics) can take an active role in researching needs and assessing hazards and their capacities. 32,33 Background -The SEQ Context…”
Section: Heatwave Managementmentioning
confidence: 99%